Toxicity effects of Cannabidiol (CBD) on immune cells - Jindaphun, Kanyaruck; Takheaw, Nuchjira; Laopajon, Witida; Pata, Supansa; Kasinrerk, Watchara (Journal of Associated Medical Sciences, 2023)
Background: Cannabis extract has a long history of being used in the treatment and prevention of several medical conditions. The utilization of cannabis extracts, whether for medical or localized purposes, is widely observed. In cannabis extract, cannabidiol (CBD) is one of the most important non-psychoactive compounds. Several studies have demonstrated that CBD has several benefits in the treatment of various medical conditions. Nevertheless, CBD has also been demonstrated to suppress both innate and adaptive immune responses. Despite CBD has claimed to have many benefits, the toxicity of CBD is often pointed out and discussed. Nonetheless, the data on the toxicity effects of CBD on immune cells are limited. Objectives: In this study, we aimed to investigate the toxicity effects of various concentrations of CBD on immune cells, including CD4 T cells, CD8 T cells, B cells, NK cells, and monocytes. Materials and methods: Various concentrations of peripheral blood mononuclear cells (PBMCs) were treated with various concentrations of CBD or relative concentrations of methanol as a diluent control for 12, 24, and 48 hrs. Cell morphology was observed using flow cytometry. The percentage of cell death in the treated cells was determined by cell viability assay. In addition, the toxic effects of CBD on PBMC sub-populations were determined by staining with fluorochromeconjugated zombie viability dye and fluorochrome-conjugated monoclonal antibodies specific to each cell sub-population. Then, the percentage of cell death in each sub-population was assessed using flow cytometry. Results: CBD at concentrations of 40 and 80 µM showed toxicity effects on PBMCs. At these concentrations, CBD induced both cell morphological changes and cell death. While 20 µM CBD induced different effects, ranging from none to mild and high toxicity. The toxicity of CBD at 20 µM concentration depends on the individual. In contrast, CBD at ten µM and below showed no toxicity to PBMCs. The observed toxic effects of CBD occurred in all sub-populations of PBMCs, including CD4 T cells, CD8 T cells, B cells, NK cells, and monocytes. Conclusion: CBD has toxicity effects on immune cells. These effects depend on CBD concentrations, PBMC concentrations, and the duration of CBD exposure. Our findings emphasize the importance of awareness for CBD users when consuming CBD.